1981
DOI: 10.1128/iai.34.3.817-827.1981
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of herpes simplex virus persistence in a human T lymphoblastoid cell line

Abstract: Persistent, dynamic-state infection with herpes simplex virus (HSV) type 1 has been maintained in human T lymphoblastoid (CEM) cells for many months after initial infection with the wild-type virus (HSVo) (input virus/cell multiplicity of 1.0). Persistently infected cells grew as well as uninfected cells, except during occasional periods of crisis (increased viral replication and cytopathic effect). Cells could survive the crisis when they were maintained for twice the usual time interval (8 to 10 rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In any case, the fact that fully susceptible cells could be cloned indicates that permissiveness is genetically dete'rmined rather than the expression of a specific moment(s) in the cell cycle. This study extends the already long list of viruses that have been shown to persist in LC lines (2,5,6,8,15). The remarkable propensity of LCs to sustain viral persistence might have important implications.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…In any case, the fact that fully susceptible cells could be cloned indicates that permissiveness is genetically dete'rmined rather than the expression of a specific moment(s) in the cell cycle. This study extends the already long list of viruses that have been shown to persist in LC lines (2,5,6,8,15). The remarkable propensity of LCs to sustain viral persistence might have important implications.…”
supporting
confidence: 58%
“…Several points emerge. First, there were wide fluctuations in virus titers, but these were not regularly cyclical nor temporally related to subculturing, as reported for other persistently infected lines (8,9,19). CVB-1 to CVB-4 stabilized at relatively high titers over 1 to 2 months of passaging, while CVB-5 fluctuated for the entire period of persistence.…”
mentioning
confidence: 68%
“…In the interaction of viruses and macrophages, it is known that some viruses, such as lactate dehydrogenase, lymphocytic choriomeningitis, parainfluenza, equine infectious anemia, Aleutian mink fever, African swine fever and avian leukosis viruses, can persist in either a replicating or nonreplicating form, without a cytopathic effect (CPE), within macrophages (14,15). However, whether or not HSV can persist in macrophages remains unknown, though HSV can persist in Chinese hamster lung cells (7)(8)(9), mouse L (17,18) and neuroblastoma cells (29), and human T and B cell lines and myeloid cell lines (2,6,24).…”
mentioning
confidence: 99%
“…infected VZV-A204 cells could be induced to produce a higher level of VZV expression by altering the growth conditions (incubation temperature or split ratio) of the cells. Cummings and coworkers (2) showed that in a lymphoblastoid cell line persistently infected with herpes simplex virus type 1, increased virus production occurs after the cell cultures are shifted from 37 to 34°C. The results of an 8-week study to determine whether cells grown at 33 rather than 37°C would contain a greater proportion of infected cells are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%